Studies on vulnerability in coastal areas: a review from analytical perspective - Mustari, Sohela; Karim, A.H.M Zehadul (Serials Publications New Delhi ( India ), 2016)
Based on existing literature, this paper, explores the vulnerability of the coastal people. The reviwed literature emphasized that vulnerability is a kind of uncertainty arising mostly from natural disasters which are different and multifarious. It discovered that the prevailing literature dealing with vulnerability of coastal people, irrespective of the cultures and the countries are unique in nature, and thus it may also be different i different parts of the same country. In addition to this, it is also hypothesized that the vulnerability of the coastal area of a developing country may further be distinct in nature as compared to a developed country. In the light of such rubrics, the paper makes an analytical discussion on vulnerability having supported by the evidences on its divergence.